Monte Carlo techniques in radiation therapy: introduction, source modelling and patient dose calculations - Verhaegen, Frank; Seco, Joao (CRC Press, Taylor & Francis Group, 2022)
"About ten years after the first edition comes this second edition of Monte Carlo Techniques in Radiation Therapy: Introduction, Source Modelling and Patient Dose Calculations, thoroughly updated and extended with the latest topics, edited by Frank Verhaegen and Joao Seco. The book aims to provide a brief introduction to the history and basics of Monte Carlo simulation, but again has a strong focus on applications in radiotherapy. Since the first edition, Monte Carlo simulation has found many new applications, which were included in detail"--
Includes bibliographical references and index
Keywords: Monte-Carlo-Simulation; Strahlendosis; Strahlentherapie; Medizinische Radiologie